Association of Vascular Endothelial Growth Factor (VEGF) in Salivary Gland Tumors - M. Zubair Jabbar, M. Mumtaz Khan, S. Fatima Tariq, Sadaf Alam, K. Nazir Arbab, A. Ahmad Khan, N. Khalid, L. Abdullah, R. Jabbar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To identify the association of vascular endothelial growth factor (VEGF) immunoexpression in the progression of salivary gland tumor. Study design: Comparative cross-sectional study Place and duration of study: Department of Pathology, Peshawar Medical College. Duration of study was six months from date of approval. Methodology: Forty five specimen of salivary gland tumor were studied in which 30 were benign and 15 were malignant. The endpoint assessment included Hematoxylin & Eosin (H&E) and VEGF immunoexpression. Results: The association of VEGF expression with salivary gland tumor was statistical significant (P<0.05). Maximum 18 samples (benign: 13, malignant: 5) were shown to have strong expression, 24 (benign: 16, malignant: 8) were shown moderate expression. Whereas, small and no expression was found in 2 (benign: 0, malignant: 2) and 1 (benign: 1, malignant: 0) sample, respectively. Conclusion: Overexpression of VEGF in both malignant and benign salivary gland tumors might be associated to progress salivary gland tumors. Keywords Benign tumor, Warthin tumor, Adenoma, Salivary gland carcinoma, Vascular endothelial growth factor